An update on developments in medical education in response to the COVID-19 pandemic: A BEME scoping review: BEME Guide No. 64. (4th March 2021) - Daniel, Michelle; Gordon, Morris; Patricio, Madalena; Hider, Ahmad; Pawlik, Cameron; Bhagdev, Rhea; Ahmad, Shoaib; Alston, Sebastian; Park, Sophie; Pawlikowska, Teresa; Rees, Eliot; Doyle, Andrea Jane; et al.
Abstract: Background: COVID-19 has fundamentally altered how education is delivered. Gordon et al. previously conducted a review of medical education developments in response to COVID-19; however, the field has rapidly evolved in the ensuing months. This scoping review aims to map the extent, range and nature of subsequent developments, summarizing the expanding evidence base and identifying areas for future research. Methods: The authors followed the five stages of a scoping review outlined by Arskey and O'Malley. Four online databases and MedEdPublish were searched. Two authors independently screened titles, abstracts and full texts. Included articles described developments in medical education deployed in response to COVID-19 and reported outcomes. Data extraction was completed by two authors and synthesized into a variety of maps and charts. Results: One hundred twenty-seven articles were included: 104 were from North America, Asia and Europe; 51 were undergraduate, 41 graduate, 22 continuing medical education, and 13 mixed; 35 were implemented by universities, 75 by academic hospitals, and 17 by organizations or collaborations. The focus of developments included pivoting to online learning ( n  = 58), simulation ( n  = 24), assessment ( n  = 11), well-being ( n  = 8), telehealth ( n  = 5), clinical service reconfigurations ( n  = 4), interviews ( n  = 4), service provision ( n  = 2), faculty development ( n  = 2) and other ( n  = 9). The most common Kirkpatrick outcome reported was Level 1, however, a number of studies reported 2a or 2b. A few described Levels 3, 4a, 4b or other outcomes (e.g. quality improvement). Conclusions: This scoping review mapped the available literature on developments in medical education in response to COVID-19, summarizing developments and outcomes to serve as a guide for future work. The review highlighted areas of relative strength, as well as several gaps. Numerous articles have been written about remote learning and simulation and these areas are ripe for full systematic reviews. Telehealth, interviews and faculty development were lacking and need urgent attention.